Effect of montmorillonite modification on resistance to thermal oxidation aging of asphalt binder - Li, Xian; Wang, Yan-Min; Wu, Shu-Jun; Wang, Hui-Ru; Liu, Xiao-Cun; Sun, Hua-Dong; Fan, Liang (Case Studies in Construction Materials, 2022)
Asphalt binder aging can cause various pavement diseases including cracking, stripping and pothole formation, which reduce the service life of asphalt pavements. Therefore, asphalt binder modification is regarded as an economical and effective method to improve its antiaging properties. In this paper, the Montmorillonite (MMT) modified asphalt binder with the additive amount of 2, 4, and 6 wt% were prepared. Rolling thin-film oven test (RTFOT) and pressure aging vessel (PAV) procedures were carried out respectively to simulate thermal oxidation aging in both short and long terms. Temperature sweep tests using a dynamic shear rheometer (DSR), Fourier transform infrared spectroscopy (FTIR), and atomic force microscopy (AFM) were performed on base and MMT-modified asphalt binders at different aging conditions. Antiaging behaviors were evaluated through the basic physical and rheological indexes, and FTIR and AFM indicators. The antiaging sensitivity and mechanism were also analysed. The results showed that 4 wt% MMT modified asphalt binder exhibits excellent antiaging properties.